Traceless Linking of Pyrroles: General Methology and Solid Phase Supported Functionalizations - Gmeiner, Peter; et al. (Synthesis-Stuttgart, 2002)
Transacetalization reaction of the diethoxymethyl (DEM) protected pyrroles 2a-f with the diol functionalized resin 3 resulted in the formation of the immobilized pyrroles 4a-f. Regioselective transformations including Pd-catalyzed coupling reactions and reductive aminations on solid phase were demonstrated.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.lphch.tracel
Keywords: DEM-protection; Palladium; Pyrroles; Solid-phase synthesis; Traceless linker